Social support and social connectedness as predictors of students’ resilience from a state university - Kevin T. Lagat; Mra Lyme F. Correche (Institute of Advanced Engineering and Science, 2026)
Mental health issues of students are among the primordial concerns of educational institutions in the post-pandemic era. Thus, resilience as an innate trait has been in frequent discussions for its positive impact on well-being. This study aimed to analyze whether social support and social connectedness were predictors of resilience among undergraduate students. Utilizing a predictive non-experimental research design, data were gathered from 402 randomly selected students from a higher education institution in eastern Philippines through standardized scales. Statistical analyses employed descriptive and inferential statistics. Results revealed that students had high levels of social support, social connectedness, and resilience and that the three variables are significantly correlated. Moreover, results of regression analysis showed that both variables significantly predicted resilience, with social support exerting a stronger influence. In conclusion, the positive influence of social support and social connectedness on students’ resilience highlights the importance of fostering supportive networks in higher education settings.